Orally bioavailable pyridine and pyrimidine-based Factor XIa inhibitors: Discovery of the methyl N-phenyl carbamate P2 prime group. Issue 10 (15th May 2016) - Corte, James R.; Fang, Tianan; Pinto, Donald J.P.; Orwat, Michael J.; Rendina, Alan R.; Luettgen, Joseph M.; Rossi, Karen A.; Wei, Anzhi; Ramamurthy, Vidhyashankar; Myers, Joseph E.; Sheriff, Steven; Narayanan, Rangaraj; et al.
Graphical abstract: Abstract: Pyridine-based Factor XIa (FXIa) inhibitor ( S )-2 was optimized by modifying the P2 prime, P1, and scaffold regions. This work resulted in the discovery of the methyl N -phenyl carbamate P2 prime group which maintained FXIa activity, reduced the number of H-bond donors, and improved the physicochemical properties compared to the amino indazole P2 prime moiety. Compound ( S )-17 was identified as a potent and selective FXIa inhibitor that was orally bioavailable. Replacement of the basic cyclohexyl methyl amine P1 in ( S )-17 with the neutral p -chlorophenyltetrazole P1 resulted in the discovery of ( S )-24 which showed a significant improvement in oral bioavailability compared to the previously reported imidazole ( S )-23 . Additional improvements in FXIa binding affinity, while maintaining oral bioavailability, was achieved by replacing the pyridine scaffold with either a regioisomeric pyridine or pyrimidine ring system.